A Conversation about Healthy Eating - A. Lesica, Nicholas (UCL Press, 2017)
What constitutes a healthy diet? Mainstream media and advertisers would like you to think that the answer to this question is complicated and controversial. But science, fortunately, tells us otherwise. A Conversation about Healthy Eating brings together all the relevant science about healthy eating in one place, and it's exactly that - a conversation; an informal discussion between a scientist and a friend about their eating habits, keeping the science firmly rooted in everyday life. The conversation moves from topics such as metabolism and digestion to gut bacteria, hormones, neuroscience and the immune system. All of these concepts are explained in accessible terms to help you understand the roles they play in maintaining a healthy diet. The conversation leads to the conclusion that staying lean and healthy simply requires avoiding the overconsumption of processed foods. While this is, of course, easier said than done, science also provides clear recommendations for how you can adapt your environment and lifestyle to make it possible. Rather than simply presenting you with the principles of healthy eating, this book will help you to develop a comprehensive understanding of the science behind the principles, including the evolutionary facts that affect the way we eat today. This understanding will allow you to ignore the noise in the media and to move forward with a healthy lifestyle that work for you.